(untitled) (American Journal of Islam and Society, 2002)
Opening Speech: Lord Dearing Lorcl Dearing (C. of E.) gave an overview of the Dearing Report, published in June 2001. He reminded the audience that historically, education has been rooted in faith. The influence of the state has been increasingly felt since 1870. He raised the issues of what justifies faith schools and distinguishes them from others. He covered the arguments of spiritual/moral education provision; and parental wish. He commented that parents look to faith schools for their discipline, caring attitude and security of values. When discussing the academic achievement argument, he commented that GCSE results in faith schools are 12% higher than in non faith schools, which still made them more attractive, if not spectacularly so. He stressed that recently, faith schools have been urged to be inclusive. They should respect people of other faiths and challenge those of no faith. Ultimately, the outcome of faith schools is measured by the quality of human beings they educate. Faith Schools: Consensus or Conflict? Keynote Speech by Professor Richard Pring (University of Oxford) Richard Pring (Catholic) stated in his introduction that there was a paradox in the fact that 33% schools in the UK are faith schools when 45% people claim to have no faith. He reviewed the arguments for faith schools: higher academic standards, including in disadvantaged communities, although the NFER research qualifies this evidence; diversity; choice: the issue is rather what are the aims we seek to promote?; ethos/value system; equality of treatment, although this could easily be reversed and lead to the abolition of all faith schools; parents v. State, cf.. "Education is too important to be put in the hands of the State." Pring considers the argument of academic excellence ...